On the Spirit of Chinese Philosophy and Its Developmental Trajectory: Reading Feng Youlan's A Short History of Chinese Philosophy - ZHANG, Rongde (Journal of Research for Christianity in China (JRCC), 2024)
Feng Youlan, A Short History of Chinese Philosophy, translated by Tu Youguang, Peking University Press, 2010. 16mo. ISBN: 9787301173954.